Analysis of Image Fusion Effect in Image Quality of Kidney Stone - Fadhila Ulfa Jhora; Freddy Haryanto; Leni Aziyus Fitri; Fourier Dzar Eljabbar Latief (Postgraduate, University of Mataram, 2022)
Kidney stones are a disease due to the buildup of substances that are not needed in the urinary system. Knowledge of the composition and type of stone is required in the treatment of action. Micro CT is one of the modalities that can be used in determining the composition of kidney stones. However, there are limitations when using single-energy micro-CT. Stone attenuation has almost the same value when using single energy, therefore it is necessary to use dual-energy CT to determine the difference in stone attenuation more precisely. The image of the dual-energy CT micro-energy stone needs to be processed before analyzing and determining the rock composition. Image fusion is one of the image processing techniques that can be used. The purpose of this study was to determine the effect of image fusion on the image quality of five kidney stones. The stages in the research carried out are collecting high energy and low energy projection image data, and performing image fusion on the two projected image data. The results obtained are first, the dual-energy CT image fusion affects the image quality which can be seen from the increase in the signal to noise ratio (SNR) value. A high SNR value provides the best image quality information